Carbon Thaw Rate Doubles When Accounting for Subsidence in a Permafrost Warming Experiment. Issue 6 (18th June 2020) - Rodenhizer, Heidi; Ledman, Justin; Mauritz, Marguerite; Natali, Susan M.; Pegoraro, Elaine; Plaza, César; Romano, Emily; Schädel, Christina; Taylor, Meghan; Schuur, Edward
Abstract: Permafrost thaw is typically measured with active layer thickness, or the maximum seasonal thaw measured from the ground surface. However, previous work has shown that this measurement alone fails to account for ground subsidence and therefore underestimates permafrost thaw. To determine the impact of subsidence on observed permafrost thaw and thawed soil carbon stocks, we quantified subsidence using high‐accuracy GPS and identified its environmental drivers in a permafrost warming experiment near the southern limit of permafrost in Alaska. With permafrost temperatures near 0°C, 10.8 cm of subsidence was observed in control plots over 9 years. Experimental air and soil warming increased subsidence by five times and created inundated microsites. Across treatments, ice and soil loss drove 85–91% and 9–15% of subsidence, respectively. Accounting for subsidence, permafrost thawed between 19% (control) and 49% (warming) deeper than active layer thickness indicated, and the amount of newly thawed carbon within the active layer was between 37% (control) and 113% (warming) greater. As additional carbon thaws as the active layer deepens, carbon fluxes to the atmosphere and lateral transport of carbon in groundwater could increase. The magnitude of this impact is uncertain at the landscape scale, though, due to limited subsidence measurements. Therefore, to determine the full extent of permafrost thaw across the circumpolar region and its feedback on the carbon cycle, it is necessary to quantify subsidence more broadly across the circumpolar region. Plain Language Summary: Permafrost soils, which are perennially frozen soils found throughout cold regions, contain vast quantities of carbon and ice. When permafrost thaws, carbon can be lost to the atmosphere, contributing to climate change. This means it is important to track permafrost thaw, which is often done using active layer thickness, or the depth of the seasonally thawed surface layer of soil. However, ice volume can be lost from thawing permafrost, causing the soil surface to drop. Conventional measurements do not account for this surface drop, and the rate of thaw could therefore be underestimated. We found that experimentally warmed soils dropped at a rate of 6 cm year −1, mostly due to loss of ice volume and also due to the loss of soil mass. When accounting for the change in soil surface height over time, the full depth of permafrost thaw was 49% greater. The increased depth of thaw resulted in more than twice as much carbon being thawed as was estimated with standard methods that did not account for subsidence. These findings suggest that permafrost is thawing more quickly than long‐term records indicate and that this could result in additional carbon release contributing to climate change. Key Points: Subsidence causes a shifting reference frame for measurements of permafrost thaw The rate of permafrost carbon thaw doubles when subsidence is accounted for Subsidence of up to 6 cm year −1 was observed in a permafrost warming experiment, due to both ice and soil loss